2018
DOI: 10.1016/j.jcv.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical, oral, and anal human papillomavirus infection in women living with HIV in Denmark – The SHADE cohort study

Abstract: Cervical and anal HPV infection were highly prevalent in WLWH. Non-16/18 hrHPV genotypes were predominant at all anatomical sites. Almost half of all hrHPV infections at the three anatomical sites could have been prevented by childhood/adolescent vaccination with the 9-valent HPV vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…It has been suggested that the prevalence of HPV in the oral cavity in HIV+ women is considerably low [19]. In our study, the prevalence of infection with any of the 12 HPV types considered was 92.5%, which contrasts with the range of 5.6%-34% in women living with HIV [12,20]. Other studies in HIV+ individuals have reported an HPV prevalence in the oral cavity Table 3.…”
Section: Plos Onecontrasting
confidence: 67%
“…It has been suggested that the prevalence of HPV in the oral cavity in HIV+ women is considerably low [19]. In our study, the prevalence of infection with any of the 12 HPV types considered was 92.5%, which contrasts with the range of 5.6%-34% in women living with HIV [12,20]. Other studies in HIV+ individuals have reported an HPV prevalence in the oral cavity Table 3.…”
Section: Plos Onecontrasting
confidence: 67%
“…in HIV+ women and 2%-31.4% in HIV-women) [20,24,33]. These results suggest that the prevalence of cervical and oropharyngeal HPV infection may vary widely according to the anatomical sites, study population, geographical region, and detection methods applied, but oropharyngeal HPV infection seems to be less common irrespective of the population group studied.…”
Section: Table 5 Discussionmentioning
confidence: 79%
“…The prevalence of cervical HPV infection was 44.3% in HIV+ women and 37.4% in HIV-women. Studies across different populations showed varying prevalenceof HPV infection, that is, 45-97.1% in HIV+ women and 44.9-86.5% in HIV-women in the cervical site [20,24,25,33]. However, the prevalence of oropharyngeal HPV infection in HIV+ women and HIV-control were 14.8% and 9.4%, respectively.…”
Section: Table 5 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-mouth oral/oropharyngeal scraping, including the cheeks, tongue, palate, tonsils, and oropharynx, was performed using a sterile brush with soft bristles; samples were stored in ThinPrep® Pap Test solution. Moreover, a gargle sample was obtained by having the participant gargle with 10 mL of 0.9% sterile saline for a total of 30 seconds (10s, rinse; 5s, gargle; 10s rinse; 5s, gargle), collected in a sterile cup and stored at -4°C [20,32]. All oral/oropharyngeal samples will be referred as "oral samples.…”
Section: Sample Collectionmentioning
confidence: 99%